Identification of IT Governance and Management Objectives and Target Process Capability Level in Government Institution - Hanafi, Ridha; Munir, Munir; Suwatno, Suwatno; Furqon, Choirul (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2023)
This study attempts to review whether the organization's IT governance and management practices are appropriate, whether other practices are needed, and the level of capability required for the practices implemented. This study uses COBIT 2019 (Control Objectives for Information and Related Technology 2019) as a reference for guideline practices and COBIT 2019 design factors as a method to identify organizational IT governance and management objectives. Based on this research, it shows that organizational IT governance and management are in accordance with national policies. However, in implementation, it still needs improvement with several other IT governance and management practices according to COBIT 2019. Based on the final results of this study after refinement of the design factor, the proposed IT objectives and practices that meet compliance with a policy are APO 13, APO 12, BAI 08, BAI 06, BAI 09, APO 14, DSS 02, and APO 07. However, adjustments still need to be made by adding some of the practices that are in line with the characteristics of the organization, which are MEA 03, DSS 05, EDM 03, and BAI 11. This study identifies appropriate IT governance and management objectives in the Province of West Java, Republic of Indonesia.